EFEKTIVITAS DEGRADASI SAMPAH ORGANIK MENGGUNAKAN LARVA BLACK SOLDIER FLY-HERMETIA - Gardis Andari; Ramdan Nurdiana (Program Pascasarjana Universitas Riau, 2022)
An increasing the volume of organic waste forming the residual impacts that can be polluted the environment. An Integrative management is needed to increase the value of organic waste and its use for several sectors such as agriculture and animal husbandry. The use of Hermetia illucens (Black Soldier Fly) larvae is an alternative for integrated waste management that can increase the value of waste processed into compost. Meanwhile, Black Soldier Fly larvae which are waste degradating agents, have the potential of high protein feed. This study was conducted to determine the effectiveness of some types of organic waste degradation using BSF larvae. The experiment was carried out using a completely randomized design with three treatments in the form of different types of organic waste. The process of waste degradation is done by placing BSF larvae taken from one broodstock. Data analysis was performed by one-way ANOVA. The results show the effectiveness of waste degradation highest value obtained on the type of rotten vegetable with 71,7 gram of media weight at the end of proccess.